Alkali-assisted membrane cleaning for fouling control of anaerobic ceramic membrane bioreactor. (September 2017) - Mei, Xiaojie; Quek, Pei Jun; Wang, Zhiwei; Ng, How Yong
Highlights: An alkali-assisted CEB cleaning method in AnMBR was developed. 0.05–1.30 mmol-NaOH/L had positive impacts on anaerobic biomass under short-term exposure. 10–20 mmol-NaOH/L backflushing significantly reduced membrane fouling rates and slightly improved methanogenic activities. 12 mmol-NaOH/L is cost-efficient and fouling-control dosage. Abstract: In this study, a chemically enhanced backflush (CEB) cleaning method using NaOH solution was proposed for fouling mitigation in anaerobic membrane bioreactors (AnMBRs). Ex-situ cleaning tests revealed that NaOH dosages ranging from 0.05 to 1.30 mmol/L had positive impacts on anaerobic biomass, while higher dosages (>1.30 mmol/L) showed inhibition and/or toxic impacts. In-situ cleaning tests showed that anaerobic biomass could tolerate much higher NaOH concentrations due to the alkali consumption by anaerobic process and/or the buffering role of mixed liquor. More importantly, 10–20 mmol-NaOH/L could significantly reduce membrane fouling rates (4–5.5 times over the AnMBR with deionized water backflush) and slightly improve methanogenic activities. COD removal efficiencies were over 87% and peaked at 20 mmol-NaOH/L. However, extremely high NaOH concentration had adverse effects on filtration and treatment performance. Economic analysis indicated that 12 mmol/L of NaOH was the cost-efficient and optimal fouling-control dosage for the CEB cleaning.